2018
DOI: 10.3390/antibiotics7040094
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Activity of Actinobacteria from the Digestive Tract of Millipede Nedyopus dawydoffiae (Diplopoda)

Abstract: Because of the spread of drug resistance, it is necessary to look for new antibiotics that are effective against pathogenic microorganisms. The purpose of this study was to analyse the species composition of actinobacteria isolated from the digestive tract of the millipedes Nedyopus dawydoffiae and to determine their antimicrobial properties. Species identification was carried out on the basis of the morphological and culture properties and the sequence of the 16S rRNA gene. Actinobacteria were grown in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
(45 reference statements)
0
4
0
3
Order By: Relevance
“…Microscopic fungi can act as pathogenic factors for millipedes, and genes involved in defense against fungi were active in all host body parts. In a recent study, eight species of antibiotic-producing Actinobacteria belonging to the genus Streptomyces were detected in the digestive tract of millipede Nedyopus dawydoffiae (Diplopoda) (Attems, 1953) 89 . We have found that lysozyme genes were produced by the host tissues as a part of probable antibacterial defense.…”
Section: Resultsmentioning
confidence: 99%
“…Microscopic fungi can act as pathogenic factors for millipedes, and genes involved in defense against fungi were active in all host body parts. In a recent study, eight species of antibiotic-producing Actinobacteria belonging to the genus Streptomyces were detected in the digestive tract of millipede Nedyopus dawydoffiae (Diplopoda) (Attems, 1953) 89 . We have found that lysozyme genes were produced by the host tissues as a part of probable antibacterial defense.…”
Section: Resultsmentioning
confidence: 99%
“…Например, представители филума Verrucomicrobiota, такие как Akkermansia muciniphila, обладают пробиотической активностью, модулируя толщину слизи в кишечнике и повышая целостность кишечного барьера (62). Бактерии филума Actinobacteriota служат продуцентами антимикробных веществ, активных в отношении патогенов (63). При этом среди бактерий филума Campilobacterota, который был представлен единственным родом Campylobacter (рис.…”
Section: среднесуточный прирост живой массы у кроликов (Oryctolagus D...unclassified
“…Агаровые среды для роста и идентификации актиномицетов, а также жидкие культуральные среды, разработаны для продуцентов антибиотиков в ФГБНУ «НИИНА» им. Г. Ф. Гаузе [5].…”
Section: материал и методыunclassified
“…Основное количество антибиотиков, образуемых актиномицетами, было описано в 1950-80 гг. После выяснения видовой принадлежности и спектров антимикробной активности мы сравнили полученные результаты с данными литературы по изучаемым видам (табл 4,5)…”
unclassified